The Influencing Factors of Transfer of Training among the Academic Staff of UiTM - S. Nik Md Salleh, N.; A. A. Wan Mohd Amin, W.; Mamat, I.; Mat Zin, S.; Mamat, M.; S. Juso, S.; S. Che Kob, C. (International Journal of Engineering and Technology, 2018)
This study examined the relationships between employee readiness (attitude, organisational commitment, abilities and motivation to learn), training design (error management and perceived importance), work environment (supervisor’s role and opportunity to use) and transfer of training among the academic staff of UiTM. This study also aimed to determine if motivation to transfer mediates the relationships between employee readiness, training design, work environment and transfer of training. By using the Structural Equation Model – Partial Least Square (SEM-PLS) for the final analysis, the results found that abilities, error management, supervisor’s role and opportunity to use had significant and positive relationships with transfer of training. The study also confirmed the mediating effects of motivation to transfer between error management, opportunity to use and transfer of training.